(untitled) (Baghdad Science Journal, 2025)
The parasite E.histolytica was first isolated from a stool sample, and then cultivated and maintained in vitro using Locke-egg medium (LEM) and Liver infusion agar medium (LIAM) . Then, the effect of some types of erythrocytes (human and sheep), on the growth and activity of the parasite in the two culture media was investigated. The parasite was able to ingest and lysis erythrocytes of human and sheep that were supplemented to the culture media and such manipulation was able to augment the reproduction rate of the cultivated E. histolytica, however, such consequence was media- and concentration-dependent. The reproduction rate was significantly increased (66.0, 57.5 and 58.6%, respectively) in LEM medium containing human erythrocytes types B at 0.11 x 106 cells/ml and O at 0.13 x 106 and 0.15 x 106 cells/ml. The sheep erythrocytes showed a similar enhancement (56.1%) at a concentration of 0.13 x 106 cells/ml. In contrast, adding erythrocytes to LIAM medium did not enhance the reproduction rate of the parasite significantly.